The study of the dentition of the Sagada Tribe - Gomez, Cynthia
This paper is a study of the dentition of a relatively pure racial stock isolated from the influences of civilization by geographic as well as cultural barriers. This is a dental-anthropologic study of a Philippine mountain tribe - the Sagada. The Sagada, as seen as a racially pure stock, exhibits an ideal occlusion characterized by a Class I molar relation, 22 mm. overjet and overbite of good interdigitation of teeth. The Sagada exhibits less decayed and missing teeth than his fellow Filipino in urban areas due to dietary habits Periodontal disease however in highly predominant due to poor oral hygiene practices.